Withaferin A targets apoptosis inhibitor cIAP1: A potential anticancer candidate - V.P. Wadegaonkar, P.A. Wadegaonkar (Journal of Applied Pharmaceutical Science)
Inhibitors of Apoptosis (IAPs) are important and well studied molecules in the cancer pathway. These are known inhibitors of apoptosis and are over expressed in many tumours where they confer chemo-resistance. The cIAP1 inhibits caspase 3 and caspase 7 and ensures suppression of apoptosis. Docking studies carried out with herbal ligand withaferin A derived from roots of Withania somnifera onto the structure of cIAP1. Withaferin A has shown strong binding affinity of -15.4988 kJ/mol with BIR domain of cIAP1 and in turn interfere in the binding of cIAP1 molecule to caspase 3 and caspase 7 and thus result into prevention of inhibition of these effecter proteins. The docking studies support the experimental outcomes and suggest that withaferin A has potential to develop as candidate molecule for cancer therapy.
Keywords: Apoptosis, Inhibitors of apoptosis, Withania somnifera.